2013
DOI: 10.1002/navi.44
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time GPS Spoofing Detection via Correlation of Encrypted Signals

Abstract: A method for detecting the spoofing of civilian GPS signals has been implemented and successfully tested in a real‐time system. GPS signal spoofing is an attack method whereby a third party transmits a signal that appears authentic but induces the receiver under attack to compute an erroneous navigation solution, time, or both. The detection system described herein provides a defense against such attacks. It makes use of correlations between the unknown encrypted GPS L1 P(Y) code signals from two narrow‐band c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 8 publications
0
44
0
Order By: Relevance
“…That is, knowledge of the local receiver positions can be quite useful if the platform rotation is known too, for example, by the use of gyros and accelerometers. The proposed GLRT detectors (10) and (12), and the mean distance detector (13) performs quite well, despite not having any knowledge of the true receiver positions. The proposed singular value detec tor (14) shows quite poor performance, and is also computationally more burdensome than the other detectors.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, knowledge of the local receiver positions can be quite useful if the platform rotation is known too, for example, by the use of gyros and accelerometers. The proposed GLRT detectors (10) and (12), and the mean distance detector (13) performs quite well, despite not having any knowledge of the true receiver positions. The proposed singular value detec tor (14) shows quite poor performance, and is also computationally more burdensome than the other detectors.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…These issues were highlighted in the so called Volpe report [1] in 2001, and much effort has been put in the research on spoofing [2][3][4] and anti spoofing techniques [5][6][7][8][9][10][11][12][13][14][15][16] in the last decade. The recent achieve ments on GPS spoofing techniques [2][3][4] have further raised these issues, and shown that it is a real threat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, numerous institutions have conducted thorough studies of this anti-spoofing technology [10,11]. A disadvantage of this method is that the signal architecture of a navigation system must be changed, which requires design changes for satellite transmitters and ground receivers.…”
Section: Signal Encryptionmentioning
confidence: 99%
“…Iranians used the "spoofing" technique which considers landing altitudes, longitudinal and latitudinal data accurately causing the drone to land to the wanted location, without needing to crack the remote-control signal and communications from the control center [27].…”
Section: Iran Hijacking Of Us Dronementioning
confidence: 99%